2022
DOI: 10.22141/2224-0713.2.80.2016.74004
|View full text |Cite
|
Sign up to set email alerts
|

Эффективность Высокодозовой Внутривенной Иммуноглобулинотерапии У детей С расстройствами Аутистического Спектра, Ассоциированными С генетическим Дефицитом Ферментов Фолатного Цикла

Abstract: неоднократно сообщали об эффективности внутривенной иммуноглобулинотерапии у некоторых детей с расстройствами спектра аутизма без уточнения критерия отбора потенциальных ответчиков на иммунотерапию. Цель исследования: оценить эффективность и безопасность высокодозовой иммуноглобулинотерапии при расстройствах аутистического спектра у детей с генетическим дефицитом фолатного цикла. Материалы и методы. Исследуемую группу составили 78 детей в возрасте от 2 до 10 лет, которые принимали в/в иммуноглобулин в дозе 2 г… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
3
0
3
Order By: Relevance
“…Besides improvements in ASD symptoms, other benefits were seen from IVIG. Six studies reported improvements in seizures with IVIG [60,67,68,76,78,81], with one study reporting a worsening of seizures when IVIG was stopped [67]. Other studies demonstrated improvements in recurrent infections [64,73], appetite [73], weight gain [73], neuropathy [76], dysautonomia [81], pro-inflammatory cytokines [22], and gastrointestinal symptoms [60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides improvements in ASD symptoms, other benefits were seen from IVIG. Six studies reported improvements in seizures with IVIG [60,67,68,76,78,81], with one study reporting a worsening of seizures when IVIG was stopped [67]. Other studies demonstrated improvements in recurrent infections [64,73], appetite [73], weight gain [73], neuropathy [76], dysautonomia [81], pro-inflammatory cytokines [22], and gastrointestinal symptoms [60].…”
Section: Discussionmentioning
confidence: 99%
“…In the 21 children with the most improvements, one (5%) lost improvements when IVIG was stopped and 12 (50%) who showed mild-to-moderate improvement lost their gains two to four months after completing therapy. Twenty-nine out of 36 patients (81%) with epilepsy had improvement in seizures and 49 out of 68 children (72%) had improvements in gastrointestinal symptoms [60]. Compared to baseline, the treated group improved in ABC irritability, hyperactivity, social withdrawal and inappropriate speech.…”
Section: Prospective Controlled Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Зокрема, у повідомленнях про клінічні випадки і результатах невеликих випробувань показана користь від застосування глюкокортикостероїдів та деяких інших протизапальних агентів у дітей із РАС, механізм дії яких вбачають саме в реалізації протизапальної дії та при-гніченні антимозкового автоімунітету [17]. Проведено щонайменше 10 клінічних досліджень із випробування імуномодулюючого агента в/в нормального імуноглобуліну людини при РАС, що, як вважають, покращує психічні функції пацієнтів завдяки пригніченню інтрацеребрального запалення та автоімунних реакцій проти мозкових автоантигенів [1,3,4,7,8,12,13,16,20,24,26]. Нещодавно інфліксимаб, препарат моноклональних антитіл проти молекули фактора некрозу пухлини альфа, продемонстрував ефективність щодо пригнічення проявів гіперактивності та гіперзбудливості в дітей із РАС, асоційованими з ГДФЦ, у контрольованому клінічному дослідженні [2].…”
Section: вступunclassified
“…1). Полученный психотропный эффект при применении инфликсимаба отличается от такового у в/в иммуноглобулина, который также продемонстрировал клиническую эффективность при расстройствах спектра аутизма, ассоциированных с генетическим дефицитом фолатного цикла [10,12]. Индуцированные инфликсимабом изменения являются более выраженными и развиваются в более сжатые сроки, однако они существенны уже по спектру положительных психотропных воздействий по сравнению с высокодозовой иммуноглобулинотерапией, оказывающей тотальное модифицироующее влияние на психику таких детей.…”
Section: імунологія та алергологія: наука і практика 3-4'2020unclassified